The Interaction between Policy Mix in Lebanon: Applications of the Nonlinear and Linear ARDL Models - Hachem, Mahmoud (International Journal of Economics and Financial Issues, 2023)
This study investigates the interaction between fiscal and monetary policies in Lebanon over the period 2001 to 2019 by using Autoregressive Distributed Lag (ARDL) and the Nonlinear Autoregressive Distributed Lag (NARDL) model introduced by Pesaran et al. (2001) and Shin et al. (2014) respectively in order to examine simultaneously the short- and long-run symmetric and possible asymmetric interactions between fiscal and monetary tools in Lebanon. The fiscal and monetary rules employed in this study are inspired from Leeper (1991, 2016 and 2018). Based on NARDL and ARDL fiscal and monetary reaction functions, Lebanese fiscal authority acts independently indicating a fiscal dominance. This situation obliged the BDL to neglect its main goal of maintaining price stability in order to support fiscal deficit by creating seigniorage revenue to balance the government accounts which in turns has led to an acceleration of inflation rates even in case of monetary contraction. The fiscal responsiveness to changes in public debt is extremely weak in Lebanon, and even is negative, and this is due to the high levels of public debt (174.3% of GDP in 2019). The empirical results indicate also that while the linear approach provides evidences of the interaction between the fiscal and monetary policies, the nonlinear approach provides more important evidences to determine in which direction this cooperation or conflict occurs between policy mix. Moreover, this paper provides new evidences of the absence of fiscal and monetary discipline rules followed by the fiscal and monetary authorities, which indicates that the policymakers in Lebanon were managing the financial and monetary policies without any specific plan or program and without any future vision or even a framework that allows these policies to be evaluated.